2020
DOI: 10.1016/j.sempedsurg.2020.150883
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and kidney disease outcomes in severely obese youth

Abstract: Bariatric surgery, an emerging treatment for severely obese youth with and without T2D, provides marked improvement in insulin resistance, beta-cell function, and central adiposity. Further, preliminary data suggest that bariatric surgery also results in significant improvement in markers of obesity-related nephropathy and DKD, beyond that which can be achieved with current medical interventions. Yet, the mechanisms whereby bariatric surgery attenuates kidney disease remain unclear. This review summarizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 108 publications
2
11
0
Order By: Relevance
“…Studies have pointed the improvement of renal function after bariatric surgery, either with increased glomerular ltration rate in patients with chronic kidney disease, or reduction of hyper ltration in patients with no evidence of kidney disease. In this regard, the present results give support to this evidence, which can summarized in improvement of renal function after bariatric surgery [23][24][25][26][27]35].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Studies have pointed the improvement of renal function after bariatric surgery, either with increased glomerular ltration rate in patients with chronic kidney disease, or reduction of hyper ltration in patients with no evidence of kidney disease. In this regard, the present results give support to this evidence, which can summarized in improvement of renal function after bariatric surgery [23][24][25][26][27]35].…”
Section: Discussionsupporting
confidence: 82%
“…In some papers one can observe, after this operative procedure, improvement of glomerular ltration rate (GFR), reduction of hyper ltration and decrease in the micro albuminuria, preventing the onset of CKD and its progression. But in others, the improvement of kidney function is not well clear [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Albuminuria significantly improved after surgery in patients with increased albuminuria at baseline (99) . Long-term cohort studies and randomized clinical trials reported that bariatric surgery prevented the development and progression of CKD and improved weight reduction, blood pressure, and metabolic control (100) .…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Albuminuria significantly improved after surgery in patients with increased albuminuria at baseline [ 98 ]. Long-term cohort studies and randomized clinical trials reported that bariatric surgery prevented the development and progression of CKD and improved weight reduction, blood pressure, and metabolic control [ 99 ]. Pharmacotherapy can be used as a component of a comprehensive strategy for managing patients with severe obesity and obesity-related comorbidities.…”
Section: Managementmentioning
confidence: 99%
“…It was reported to improve insulin resistance ( Gumbs et al, 2005 ; Rao et al, 2012 ); however, the mechanism remains unclear. Roux-en-Y gastric bypass surgery can effectively relieve T2DM and related metabolic complications while treating morbid obesity ( Bjornstad et al, 2020 ; Vangoitsenhoven et al, 2020 ). In a long-term follow-up study, it was found that patients with T2DM and impaired glucose tolerance maintained normal blood glucose levels after gastric bypass surgery.…”
Section: Introductionmentioning
confidence: 99%